2013
DOI: 10.1167/iovs.13-13081
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Parameter Variations in Patients With Human Immunodeficiency Virus

Abstract: Our study showed that patients with HIV have significant variations in retinal vasculature. Retinal vascular imaging may offer further insight into the pathophysiology behind HIV-related vascular disease in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…This study aimed to assess retinal structure and visual function in a group of perinatally HIV-infected children, compared to a group of matched healthy controls. Subtle structural retinal changes and visual dysfunction, termed HIVassociated neuroretinal disorder, have been described in HIVinfected adults on cART without infectious retinitis [1][2][3][4][5][6][7][8][9][10]14,16,17,[51][52][53][54][55][56][57][58][59] ; however, data on this subject in HIVinfected children are limited and derived from one study group. 22,23 This is the first study assessing individual retinal layer thicknesses and exploring associations between various HIV-and cART-related factors and ocular parameters in HIVinfected children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed to assess retinal structure and visual function in a group of perinatally HIV-infected children, compared to a group of matched healthy controls. Subtle structural retinal changes and visual dysfunction, termed HIVassociated neuroretinal disorder, have been described in HIVinfected adults on cART without infectious retinitis [1][2][3][4][5][6][7][8][9][10]14,16,17,[51][52][53][54][55][56][57][58][59] ; however, data on this subject in HIVinfected children are limited and derived from one study group. 22,23 This is the first study assessing individual retinal layer thicknesses and exploring associations between various HIV-and cART-related factors and ocular parameters in HIVinfected children.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in cART-treated individuals with well-suppressed HIV infection and absence of opportunistic infections, functional and structural retinal abnormalities have been reported, such as a subtle loss of color vision and/or contrast sensitivity, visual field deficits, and a thinner retinal nerve fiber layer (RNFL) thickness. [1][2][3][4][5][6][7][8][9][10] These changes are thought to be part of a ''HIV-associated neuroretinal disorder'' (HIV-NRD) and may be mediated by several processes, such as longstanding microvasculopathy, [11][12][13][14][15][16][17] direct damage of neural tissue by HIV and/or cART, [18][19][20] and chronic (para)inflammation. 21 It is unclear whether such retinal changes are also present in cART-treated HIV-infected children (without a history of ocular opportunistic infections).…”
mentioning
confidence: 99%
“…2). Retinal vascular calibre was measured based on the revised Knudtson-Parr-Hubbard protocol (Li et al 2011;Tan et al 2013). The central retinal arteriolar and venular equivalents were recorded, representing the average arteriolar and venular calibres of each eye.…”
Section: Fundus Image Analysismentioning
confidence: 99%
“…However this finding is not backed by the study [60], which states that there is no association between the length of HAART and the decrease in CRAE from their data.…”
Section: Datamentioning
confidence: 77%
“…As part of the micro-circulation, the retinal vasculature provides an access to examine and monitor changes and conditions related to the circulation, which can reflect physiological and metabolic changes of HIV patients. Recent studies have shown that the retinal vasculature changes as a result of HIV infection, as well as HAART treatment [58,59], including arteriolar and venular vessel widths, the branching angle and vascular tortuosity [60,61]. However, some of findings are inconclusive, and the cause of these changes is not established currently.…”
Section: Diseases Related With Retinal Vascular Changesmentioning
confidence: 99%